Beyond the Clichés in the Study of Disappearance - María Martínez; Iñaki Robles Elong; Ivana Belén Ruiz-Estramil (Oñati Socio-Legal Series)
In the study of disappearance, some issues have imposed as mandatory themes of research becoming clichés. In this article, we examine some of those clichés —irrepresentability, unspeakability and impossibility of testimony, disappeared spaces, bare life and agency— with a double objective: on the one hand, inquire into the type of analysis that each cliché allows, but also limits; and, on the other hand, propose that some openings from those clichés are necessary to the study of forms of disappearance that go beyond the original, meaning, forms of disappearance beyond the definition by international law as “enforced disappearance”. We argue that although contemporary forms of disappearance have a common genealogy with the original and share some of its paradoxes (absence, void, paradox, inexistence, invisibility), they requires a more complex analysis.